The Role of Catholic Secular Clergy in Polish Pastoral Care Between the Wars - Czarnowski, Robert (Studia Teologiczne Białystok Drohiczyn Łomża, 2024)
The article presents the role of Polish secular clergy in the provision of pastoral care between the world wars. The study notes that Poland's regaining independence in 1918 was a strong motivation to introduce indispensable changes in the structure of parishes and training of the clergy. Such changes were discussed during the Extraordinary Session of the Polish Bishops' Conference in Gniezno, convened on 17-20 September 1928. The bishops appraised the general pastoral situation in Poland. The article moreover addresses questions of the operation of parishes and the priests' spirituality. Special attention was paid to the problems faced by diocesan clergy and a proposal for their vita communis. Another significant question addressed by the study is the legislation of the first Polish plenary synod.